Desarrollo disciplinar de la enfermería (2002)
ABSTRACT: Explicitly considers, the development of the nursing discipline; first, the concept of discipline and it importance for one scientific community. Second, indicates the frontier of the nursing discipline with other disciplines in the area of health. The third point, shows dynamic in the development of the nursing discipline. Finally, it presents some considerations about the research required and the needs for the application of the knowledge produced, because the question to be in the future to professional nurses, it will not inquiry about what is done, but what is known.